50th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2014
DOI: 10.2514/6.2014-3442
|View full text |Cite
|
Sign up to set email alerts
|

Exploring advanced technology gas turbine engine design and performance for the Large Civil Tiltrotor (LCTR)

Abstract: A Large Civil Tiltrotor (LCTR) conceptual design was developed as part of the NASA Heavy Lift Rotorcraft Systems Investigation in order to establish a consistent basis for evaluating the benefits of advanced technology for large tiltrotors. The concept has since evolved into the second-generation LCTR2, designed to carry 90 passengers for 1,000 nautical miles at 300 knots, with vertical takeoff and landing capability. This paper explores gas turbine component performance and cycle parameters to quantify perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Independent system studies performed by NASA and Boeing showed that advanced turboshaft engines with VSPT would have the benefits of a 13% lower Take-off Gross Weight (TOGW) and a 25-28% lower fuel burn for the NASA RVLT LCTR mission [67][68][69][70][71][72]. At takeoff, the LCTR main rotors and the VSPTs operate at 100% speed, while at cruise the rotors tilt forward and the VSPTs are slowed to 54% speed to enable higher efficiency.…”
Section: Variable Speed Power Turbine (Vspt) -Enabling Future Vertical Lift Propulsion Requirementsmentioning
confidence: 99%
“…Independent system studies performed by NASA and Boeing showed that advanced turboshaft engines with VSPT would have the benefits of a 13% lower Take-off Gross Weight (TOGW) and a 25-28% lower fuel burn for the NASA RVLT LCTR mission [67][68][69][70][71][72]. At takeoff, the LCTR main rotors and the VSPTs operate at 100% speed, while at cruise the rotors tilt forward and the VSPTs are slowed to 54% speed to enable higher efficiency.…”
Section: Variable Speed Power Turbine (Vspt) -Enabling Future Vertical Lift Propulsion Requirementsmentioning
confidence: 99%
“…The turboshaft motor drives the generator at a constant speed. Turboshaft engine power requirements as a function of vehicle speed are shown in Figure 3, where power levels are described in Table 1 based on engine ratings defined in Ref (10). Motor and generator power required refers to electric motor and turboshaft engine requirements for the mission respectively, and do not account for auxiliary power needs and losses.…”
Section: T II System Definition and Requirementsmentioning
confidence: 99%
“…Work continues on gas turbines to further improve efficiency and apply these gains to rotorcraft design (Snyder, 2014;Hendricks, Jones, and Gray, 2014). There are still significant gains to be achieved through turbomachinery component efficiency.…”
Section: Ongoing Propulsion Research Within Nasamentioning
confidence: 99%